The Strategy of BPJS Ketenagakerjaan Banda Aceh Branch in the Socialization of the Non-wage Recipient Program - Rahmat Arfan; Rila Maufira; Indra Akbar (Telaah Bisnis, 2022)
This study aims to discuss the strategies implemented by BPJS Ketenagakerjaan Banda Aceh Branch Office in disseminating the Non-Wage Recipient program and to find out the obstacles of this program. The theory used in this paper is the promotion mix model which includes: sales promotion, personal selling, direct marketing, advertising, and public relations. This study uses qualitative analysis methods. This paper uses certain data collection techniques such as an interview with respondents and documentation supporting the research.The results showed that the strategy BPJS Ketenagakerjaan Banda Aceh Branch used in socializing the Non-Wage Recipient Program or BPU program was by advertising or promoting the benefits of the BPJS Ketenagakerjaan program for informal workers in various media. The second strategy is personal selling. The third strategy is public relations. The fourth strategy is direct marketing through the Market. The last strategy is sales promotion through socialization in informal worker forums. There are four obstacles faced by BPJS Ketenagakerjaan Banda Aceh Branch in conducting socialization this program, it is the public's view about BPJS is not an Islamic product, competition with commercial insurance, lack of firmness from the government.